2019
DOI: 10.1111/jorc.12303
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Chronic Kidney Disease, Symptoms and Health‐Related Quality of Life: A Systematic Review

Abstract: A. (2020). The relationship between chronic kidney disease, symptoms and healthrelated quality of life: a systematic review. Journal of Renal Care 46(2), 74-84. S U M M A R YBackground: People with chronic kidney disease (CKD) experience a wide range of symptoms due to reduced kidney function. As the disease progresses these symptoms become more burdensome and often negatively affect a person's health-related quality of life (HRQoL). Objective: To examine the evidence of symptoms and HRQoL in CKD stages 1-5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
3
23
1
1
Order By: Relevance
“…Former studies clearly showed that end-stage renal disease and dialysis are associated with low QoL [15,16,40,41], and few studies reported that even early stages of CKD may significantly affect QoL [17][18][19][20]. Our findings are clearly different from that reported in a recent cross-sectional analysis of the Irish Longitudinal Study on Ageing showing that creatinine-based eGFR may contribute little to QoL [42].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Former studies clearly showed that end-stage renal disease and dialysis are associated with low QoL [15,16,40,41], and few studies reported that even early stages of CKD may significantly affect QoL [17][18][19][20]. Our findings are clearly different from that reported in a recent cross-sectional analysis of the Irish Longitudinal Study on Ageing showing that creatinine-based eGFR may contribute little to QoL [42].…”
Section: Discussioncontrasting
confidence: 99%
“…The few studies investigating the impact of early stages of CKD on QoL show that QoL may be poorer than that of the general population, but better than for CKD patients on dialysis [18,19]. In a recent systematic review, Yapa et al [20] showed that health-related QoL may worsen when CKD symptoms (e.g. fatigue, exhaustion and drowsiness) appear.…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted in a recent systematic review (Yapa et al, 2020), more studies are needed to investigate how symptoms and HRQoL change across the CKD trajectory. This study, therefore, aimed to compare symptom burden and HRQoL and to examine the relationship between these at CKD G3b, G4, G5 and G5D.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Although the participants in these two studies were limited to those with CKD G4, G5 and G5D, both studies found that a decrease in HRQoL when symptoms increased. As highlighted in a recent systematic review (Yapa et al, 2020), more studies are needed to investigate how symptoms and HRQoL change across the CKD trajectory. This study, therefore, aimed to compare symptom burden and HRQoL and to examine the relationship between these at CKD G3b, G4, G5 and G5D.…”
Section: Introductionmentioning
confidence: 99%
“…HR-QOL is defined as an individual or group’s perceived physical and mental health over the duration of a disease 11 . Since HR-QOL is relative to the severity of the patient’s perceived symptoms, HR-QOL itself can be a clinical outcome indicator 12 . CKD is a disease with particularly low HR-QOL.…”
Section: Introductionmentioning
confidence: 99%